EFEKTIVITAS HASHTAG TIKTOK TRAVEL X WONDERFUL INDONESIA PADA 10 DESTINASI BALI BARU - Anggreani, Riza Bella; Suardana, I Wayan; Wikanatha Sagita, Putu Agus (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 2 (2022): Jurnal IPTA (December 2022)DO - 10.24843/IPTA.2022.v10.i02.p09, 2023)
This study aims to determine the effectiveness of promotion through the hashtag Tiktok Travel X Wonderful Indonesia on 10 New Bali Destinations. In this study, the determination of the sample used the purposive sampling . Data was collected by distributing online questionnaires through social media to 99 respondents, indirect observation, and literature study. The data analysis techniques used are descriptive quantitative analysis using a Likert scale, simple tabulation analysis and the AIDA model. The results of this study indicate that based on the results of research on the characteristics of Tiktok social media users who visited 10 New Bali Destinations, which were dominated by Tiktok social media users from East Java, aged between 18–24 years, female, high school graduates, by profession as a student, has a relatively low monthly income of Rp. 500,000.00 – Rp. 2,500,000.00 While the results of research on the effectiveness of tourism promotion through the hashtag Tiktok Travel X Wonderful Indonesia in 10 New Bali Destinations have an average AIDA score of 3.05 with a scale range of 2.51-4.00 in the effective category., so it can be said that tourism promotion through the hashtag Tiktok Travel X Wonderful Indonesia on 10 New Bali Destinations is able to attract attention ( Attention ), generate interest ( Interest ), raise desire ( Desire ), as well as convincing Tiktok social media users to determine their envoy is to visit directly to 10 New Bali Destinations.